2016
DOI: 10.1016/j.clim.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling complement C1s activation from C1q binding in apoptotic cell phagocytosis and immunosuppressive capacity

Abstract: Complement activation contributes to inflammation in many diseases, yet it also supports physiologic apoptotic cells (AC) clearance and its downstream immunosuppressive effects. The roles of individual complement components in AC phagocytosis have been difficult to dissect with artificially depleted sera. Using human in vitro systems and the novel antibody complement C1s inhibitor TNT003, we uncoupled the role of the enzymatic activation of the classical pathway from the opsonizing role of C1q in mediating a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…In addition to promoting phagocytosis, complement activation results in the production of anaphylatoxins, C3a and C5a, that cause chemotaxis of immune cells and glia, promote proinflammatory polarization and cytokine production, and stimulate oxidative bursts (reviewed in Schraufstatter, Khaldoyanidi, & DiScipio, 2015;Thielens, Tedesco, Bohlson, Gaboriaud, & Tenner, 2017). C1q also has immunoregulatory properties that suppress proinflammatory cytokine production and limit inflammation when clearing apoptotic cells and debris, but how this anti-inflammatory effect is received by immune cells may depend on their differentiation state and the surrounding inflammatory milieu (Colonna, Parry, Panicker, & Elkon, 2016;Fraser, Laust, Nelson, & Tenner, 2009 that C1q is involved in synapse removal or clearance of cellular debris at the injection site early on, but that other "eat me" signals also exist that can fully compensate for the loss of C1q. The 7 days time point used for western blots was aimed at assessing synapse loss at an earlier time point, but it also leaves time for compensatory mechanisms to compensate for the loss of C1q.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting phagocytosis, complement activation results in the production of anaphylatoxins, C3a and C5a, that cause chemotaxis of immune cells and glia, promote proinflammatory polarization and cytokine production, and stimulate oxidative bursts (reviewed in Schraufstatter, Khaldoyanidi, & DiScipio, 2015;Thielens, Tedesco, Bohlson, Gaboriaud, & Tenner, 2017). C1q also has immunoregulatory properties that suppress proinflammatory cytokine production and limit inflammation when clearing apoptotic cells and debris, but how this anti-inflammatory effect is received by immune cells may depend on their differentiation state and the surrounding inflammatory milieu (Colonna, Parry, Panicker, & Elkon, 2016;Fraser, Laust, Nelson, & Tenner, 2009 that C1q is involved in synapse removal or clearance of cellular debris at the injection site early on, but that other "eat me" signals also exist that can fully compensate for the loss of C1q. The 7 days time point used for western blots was aimed at assessing synapse loss at an earlier time point, but it also leaves time for compensatory mechanisms to compensate for the loss of C1q.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the last 15 years confirmed that C1q enhances phagocytosis of a variety of apoptotic cells by multiple cell types both in vitro and in vivo (reviewed in (Galvan et al, 2012a)). Interestingly, most recently Elkon and colleagues, using an inhibitor of C1s, demonstrated that C1q facilitates apoptotic cell engulfment independent of classical pathway activation (Colonna et al, 2016). …”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
“…While there have been some studies suggesting the possibility of a direct C1q interaction with T cells, more definitive investigations are needed (reviewed in (Clarke and Tenner, 2014)). The recent confirmation of the predominant role of C1q (rather than C1 activation and C3b deposition) on clearance and immunosuppression of apoptotic cells should direct therapeutic intervention in SLE and other autoimmune diseases (Colonna et al, 2016). …”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
“…A recent study confirmed the important role of C1q as a bridging molecule between apoptotic cells and phagocytes and additionally pointed out the less studied role of C1q in controlling the phagocyte inflammatory status . C1q has previously been shown to promote immune tolerance and to resolve inflammation by modulating the cytokine release by phagocytes toward an immunomodulatory/anti‐inflammatory direction . Remarkably, C1q appears to have an inhibitory effect on inflammasome activation in macrophages .…”
Section: Dying Cells Are Recognized By Complement Initiatorsmentioning
confidence: 82%